Hyparrhenia hirta: A potential protective agent against hematotoxicity and genotoxicity of sodium nitrate in adult rats. Issue 11 (17th April 2014) - Bouaziz‐Ketata, Hanen; Salah, Ghada Ben; Mahjoubi, Amira; Aidi, Zied; Kallel, Choumous; Kammoun, Hassen; Fakhfakh, Faiza; Zeghal, Najiba
ABSTRACT The present study was carried out to examine the adverse hematotoxic and genotoxic effects of water nitrate pollution on male adult rats and the use of hyparrhenia hirta methanolic extract in alleviating these effects. Sodium nitrate (NaNO3) was administered to adult rats by oral gavage at a dose of 400 mg kg−1 bw daily for 50 days, while hyparrhenia hirta methanolic extract was given by drinking water at a dose of 1.5 mg mL−1 (200 mg kg−1 bw). The NaNO3‐treated group showed a significant decrease in red blood cell count, hemoglobin and hematocrit and a significant increase in total white blood cell, in neutrophil and eosinophil counts. Platelet count, mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration remained unchanged in treated groups compared to those of controls. Meanwhile, the results showed a marked reduction in the antioxidant enzyme activities, such as superoxide dismutase, catalase, and glutathione peroxidase, along with an elevation in the level of lipid peroxidation and a reduction in the total glutathione content, indicating the induction of oxidative stress in the erythrocytes of NaNO3‐treated group. Interestingly, NaNO3 treatment showed a significant increase in the frequencies of total chromosomal aberrations, aberrant metaphases and micronucleus in bone‐marrow cells. The oxidative stress induced by nitrate treatment might be the major cause for chromosomal rearrangements as free radicals leading to DNA damage. Hyparrhenia hirta methanolic extract appeared to be effective against hematotoxic and genotoxic changes induced by nitrate, as evidenced by the improvement of the markers cited above. © 2014 Wiley Periodicals, Inc. Environ Toxicol 30: 1275–1284, 2015.